2012
DOI: 10.1021/pr3005666
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Evaluation of Inflammatory Proteins in Rat Spleen Interstitial Fluid and Lymph during LPS-Induced Systemic Inflammation Reveals Increased Levels of ADAMST1

Abstract: The spleen is a part of the immune system and is involved in the response to a systemic inflammation induced by blood borne pathogens that may induce sepsis. Knowledge about the protein composition of the spleen microenvironment in a control situation and during systemic inflammation may contribute to our understanding of the pathophysiology of sepsis. To our knowledge, the proteome of the fluid phase of the spleen microenvironment has not previously been investigated. In order to access the proximal fluid sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 47 publications
1
20
1
Order By: Relevance
“…Another interesting work reported significant levels of ADAMTS1 in interstitial fluid of spleens, lymph nodes and plasma after a systemic lipopolysaccharide-induced inflammation 48 . At this point, we should recall the original cloning of mouse Adamts1 in a cachexia model 6 , a phenomena with a recognized inflammatory component.…”
Section: Discussionmentioning
confidence: 98%
“…Another interesting work reported significant levels of ADAMTS1 in interstitial fluid of spleens, lymph nodes and plasma after a systemic lipopolysaccharide-induced inflammation 48 . At this point, we should recall the original cloning of mouse Adamts1 in a cachexia model 6 , a phenomena with a recognized inflammatory component.…”
Section: Discussionmentioning
confidence: 98%
“…ADAMTS1 is necessary for normal growth, female fertility, and kidney, adrenal and female reproductive organ structure and function [46]. Recently, it was shown that LPS dramatically increased the synthesis of ADAMTS1 within the splenic lymph and interstitial fluid to a concentration that was much higher than that of plasma, suggesting that the spleen is a major source of ADAMTS1, and that this metalloprotease is involved in the endotoxin-induced disease process [47]. Within the brain, metalloproteases play a key role in controlling blood brain barrier permeability during LPS-induced inflammation, and ADAMTS1 may have a role in regulating neural plasticity, as null female mice have a selective decline of synaptic protein levels in the frontal cortex [48].…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of sepsis (cecal ligation and puncture), proteomic analysis of mesenteric lymph revealed 158 proteins significantly changed, including elevations in ApoE, annexin-1, S100A8/9, and the lipocalin NGAL (1208). Analysis of postdnodal lymph from rats subjected to LPS exposure revealed elevations in inflammatory cytokines and the disintegrin ADAMTS1 (827). Findings from these proteomic studies can be influenced by choices of models and methodology.…”
Section: Interstitial Flow and Lymph Formationmentioning
confidence: 99%